Efektivitas Keberlanjutan Pukat Cincin (Purse Seine) di Pelabuhan Perikanan Pantai Pulau Baai Bengkulu - Futra, Febby Dwi; Yuwana, Yuwana; Johan, Yar; Brata, Bieng; Bakhtiar, Deddy (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2024)
The effectiveness of the sustainability of purse seines at the Baai Island Bengkulu Coastal Fishing Harbor must pay attention to all aspects, namely ecology, economics, technology, social and institutional. The aims of this research are 1) identifying Purse seine fishing gear, 2) analyzing the sustainability effectiveness of Purse seine, and 3) formulating strategies for the sustainability effectiveness of Purse seine. This research was carried out from March to September 2021 located at the Baai Island Coastal Fishing Harbor, Bengkulu. The research method used is a survey method. The data used are primary and secondary data. Respondents as sources of information came from government elements, fishermen and academic elements who used purposive sampling techniques. Data analysis used the Rapid Appraisal For Fisheries (RAPFISH) method. From the research results, it was found that the sustainability effectiveness of purse seines at the Baai Island Bengkulu Coastal Fishing Harbor was at a value of 65.31 (quite sustainable). The sensitive attributes that influence the effectiveness of sustainability are the application of environmentally friendly fishing technology, counseling for fishermen, employment status as a fisherman, and the use of destructive fishing tools. The policy strategy to increase the effectiveness status of the sustainability of Purse seine is carried out by means of the need to implement environmentally friendly fishing technology for Purse seine fishermen, outreach to fishermen who can provide good education to Purse seine fishermen. in the form of science and technology that can be applied by Purse seine fishermen, the welfare of Purse seine fishermen can be achieved if fishermen have employment status as full fishermen, and outreach to Purse seine fishermen regarding the prohibition on the use of fishing gear destructive Keywords: Aspects of soil, climate, land suitability, ponds, water quality and resources